Corporate Governance and Tax Avoidance: A Systematic Literature Review and Bibliometric Assessment of Research Trends - Nanik Lestari; Bandi .; Eko Arief Sudaryono; Lulus Kurniasih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study provides a systematic literature review and bibliometric assessment of research on corporate governance and tax avoidance to examine its intellectual development, dominant themes, theoretical foundations, and future research directions. Using the PRISMA framework, 142 peer-reviewed articles indexed in Scopus were analyzed using bibliometric techniques and qualitative synthesis. The findings indicate that corporate governance mechanisms, including board characteristics, audit committee effectiveness, ownership structure, and institutional monitoring, remain the primary determinants of corporate tax behavior. While Agency Theory continues to dominate the literature, emerging perspectives such as Stakeholder Theory, Institutional Theory, and Legitimacy Theory have gained increasing attention. The review further reveals a growing research focus on Corporate Social Responsibility (CSR), Environmental, Social, and Governance (ESG) practices, digital governance, artificial intelligence, blockchain technology, and tax risk management, reflecting a shift toward sustainability and technology-oriented governance frameworks. The study contributes to the literature by integrating fragmented evidence into a comprehensive framework and identifying critical research gaps. Although limited to Scopus-indexed publications, the findings offer valuable insights for researchers, policymakers, and practitioners and highlight the need for future studies that integrate governance, sustainability, digital transformation, and tax risk perspectives to understand corporate tax behavior better.